2019
DOI: 10.1002/jmor.21039
|View full text |Cite
|
Sign up to set email alerts
|

The adult musculature of two pseudostomid species reveals unique patterns for flatworms (Platyhelminthes, Prolecithophora)

Abstract: We analyzed the adult musculature of two prolecithophoran species, Cylindrostoma monotrochum (von Graff, 1882) and Monoophorum striatum (von Graff, 1878) using a phalloidin‐rhodamine technique. As in all rhabdithophoran flatworms, the body‐wall musculature consisted of three muscle layers: on the outer side was a layer of circular muscle fibers and on the inner side was a layer of longitudinal muscle fibers; between them were two different types of diagonally orientated fibers, which is unusual for flatworms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…When amputated in the middle of the body the restored pharynx had a diameter of ca. 99 +/− 7.5 µm, while the original size is ca 150 +/− 6.4 μm [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…When amputated in the middle of the body the restored pharynx had a diameter of ca. 99 +/− 7.5 µm, while the original size is ca 150 +/− 6.4 μm [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transverse muscle fibers have also been identified in cestodes (Mair, Maule, Shaw, & Halton, 1998). Some authors noted the presence of transverse muscles in other flatworms; for example, Grosbusch et al (2019) identified bundles they called “transverse” in the posterior and anterior body regions of two prolecithophorans (Platyhelminthes), Cylindrostoma monotrochum and Monoophorum striatum . In the free‐living turbellarian Dugesia japonica (Platyhelminthes), transverse muscle fibers were also observed distributed across the body (Orii et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We collected adult specimens of all six prolecithophoran species [ Cylindrostoma fingalianum (Claparède, 1861); Cylindrostoma monotrochum (von Graff, 1882); Monoophorum striatum (Graff, 1878); Plagiostomum koreni Jensen, 187 8 ; Acmostomum dioicum Metschnikoff, 1865; Vorticeros auriculatum (Müller, 1784)] from brown algae in the port of Punat, Krk, Croatia (45°01′23”N 14°37′41″E) in March 2016, October 2016, 2017, May 2018, and in October 2019. The extraction and maintenance of the animals were made according to Grosbusch et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…For staining, nine adult C. fingalianum (Figure 1(a)), five adult C. monotrochum (Figure 2(a)), 12 adult M. striatum (Figure 3(a)), six adult P. koreni (Figure 4(a)), 14 adult A. dioicum (Figure 5(a)), and seven adult V. auriculatum (Figure 6(a)) were used. Cylindrostoma monotrochum and M. striatum were stained according to Grosbusch et al (2019). Four individuals of V. auriculatum were stored at −20°C before staining; two in ethanol and two in aceton.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation